Writing as resistance: transnational women’s testimonies of the carceral seventies - Purkayastha, Sharmila (Geographies of gendered punishment, 2024)
The carceral geographies of the seventies have left significant footprints in the global south. Mapping some of these carceralities through testimonies of women political activists associated with left-wing movements, this essay examines forms of impunity and modes of resistance through a transnational study of three prison accounts from India, Morocco and Uruguay.